Helmintos e ácaros nasais parasitos de Pitangus sulphuratus (Passeriformes: Tyrannidae), bem-te-vi, no Rio Grande do Sul - Mendes, Mariana de Moura (2011)
The Great Kiskadee, Pitangus sulphuratus (Linnaeus, 1766) (Tyrannidae), occurs only in the Americas, is distributed from the United States (Texas) to Argentina. It is the most popular bird species of Brazil and Rio Grande do Sul, being easily recognized by its onomatopoeic song, vivid colorations and aggressive behavior in a dispute over territory and when guarding the nest. These birds can be found in a wide variety of habitats such as crop fields, towns, orchards, woods and edge of aquatic environments, such as margins of ponds, streams, rivers and dams. They have skills to identify foods in natural environments and exploring food resources of anthropic origin, which contributes to its efficiency in colonizing urban environments and their abundance in various environments. The Great Kiskadee can be considered an omnivorous species, and its flexibility in their food can influence their helminthofauna, since the majority of gastrointestinal parasites are acquired through ingestion of food. Due to lack of information on parasite biodiversity of P. sulphuratus, this work was developed aimed to characterize and disseminate the helminthofauna and nasal mites that parasites the Great Kiskadee, and to calculate the parameters of prevalence, average intensity and average abundance of parasitism. Were examined 78 specimens of P. sulphuratus belonging to the municipality of Pelotas and adjacent municipalities, among those who came to death at the Center for Wildlife Rehabilitation Center and Triage of Wild Animals (NURFS / CETAS / UFPel) and were run over, collected on the highways. At the Laboratory of Parasitology of Wild Animals, Department of Microbiology and Parasitology, birds were necropsied to collect helminths and nasal mites. Helminths found and their parameters of prevalence (P), average abundance (AM) and average intensity (IM) were Dispharynx nasuta (P = 3.85%, AM = 0.10, IM = 2.66), Acuaria Mayor (P = 7 , 69%, AM = 0.18, IM = 2.33), representatives of the subfamily Capillariinae (P = 10.26%, AM = 0.22, IM = 2.12), Eucoleus sp. (P = 10.26%, AM = 0.38, IM = 3.75), Aproctella sp. (P = 6.41%, AM = 0.08, MI = 1.2), Syngamus sp. (P = 7.69%, AM = 0.26, IM = 3.33), Lophosicyadiplostomum nephrocystis (P = 14.10%, AM = 3.18, MI = 22.54), Lutztrema sp. (P = 3.85%, AM = 0.08, IM = 2), Echinostoma sp. (P = 2.56%, AM = 0.15, IM = 6), Centrorhyncus spp. (P = 48.72%, AM = 3.87, IM = 7.95), and representatives of the order Ciclophyllidae (Cestoda) (P = 2.56%). The nasal mites Ptilonyssus spinosus were found with 12.82% prevalence, AM = 1.13, IM = 8.8, sex ratio 4:2, ♀ / ♂ and Sternostoma longisetosae, 5.13%, 0.13 and 2.5, respectively, all specimens were females. A parasitic association between the two species was observed in only one P. sulphuratus. Pitangus sulphuratus features a new host for helminths Dispharynx nasuta, Acuaria mayor, Capillariinae, Eucoleus sp. Aproctella sp. Syngamus sp. (Nematoda), Lutztrema sp. and Echinostoma sp. (Trematoda). That expands the area of occurrence of A. Mayor and L. nephrocystis for the state of Rio Grande do Sul.